THE EFFECT OF CAPITAL STRUCTURE, PROFITABILITY AND CORPORATE GOVERNANCE ON TAX AVOIDANCE AND ITS IMPACT ON COMPANY VALUE: AN EMPIRICAL STUDY OF PUBLIC COMPANIES IN INDONESIA, MALAYSIA AND THE PHILIPPINES - Maharani Dewi; Rio Johan Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study discusses the impact of capital structure, especially profitability, on tax avoidance practices in companies and the role of corporate governance in controlling these practices. The problem raised is how debt as source financing provides incentives for tax shield benefits that encourage companies to manage taxes aggressively to increase the Company's Value. The content of the study highlights the relationship between corporate profitability and tax management motivation, as well as the importance of strong governance mechanisms as a control of excessive tax avoidance so as not to reduce investor confidence and the company's market value. The research method uses a comparative approach between countries with a sample of companies in Indonesia, Malaysia, and Thailand, which have different tax governance and regulatory characteristics. The results show that Indonesia tends to experience more aggressive tax avoidance due to evolving supervision, Malaysia implements more transparent governance and taxation so that tax avoidance is more controlled, while Thailand occupies a moderate position with improved governance that has begun to be implemented. In conclusion, the success of tax avoidance management does not only depend on capital structure and profitability, but is highly determined by the quality of corporate governance and supervision in each country. Increased transparency and consistent regulation are essential to create an optimal balance between tax efficiency and the continuity of a Company's operations.